Planejamento nas organizações estaduais de assistência técnica e extensão rural - ATER: percepções do alinhamento estratégico frente às políticas setoriais - Scholz, Gustavo Adolfo Gomes (2014)
The Technical Assistance and Rural Extension Law provides for technical assistance and rural extension in the agriculture sector, which is one of the main economic sectors in Brazil due to the centralized planning model used since the 1980 decade. The Technical Assistance and Rural Extension State organizations, as well as private extension, science and technology, credit policies, foment and infrastructure, play a very important role in the Brazilian economy. The re-democratization and opening of the Brazilian market to international markets in the 80s helped the creation of a new public management that provided the modernization of public administration processes. On the other hand, economic crises stimulated new social movements seeking to valorize family farm that started to be part of policy agenda, thus encouraging the creation of sector policies and programs such as: National Program for Family Farm Strengthening (1996), Technical Assistance and Rural Extension National Policy (2003) and Technical Assistance and Rural Extension Law (2010). When analyzing organizations’ planning based on the Law guiding, we sought to identify the planning strategic alignment extent to meet the sector national directives. Besides the content analysis methodology, our study also used Pettan methodology (2010 – adapted from BETHLEM, 2004) via questionnaires filled out by managers of twenty seven (27) Technical Assistance and Rural Extension organizations. Results show that 60% of them used concomitantly tactic-operational planning and the Pluri- annual planning -PAP (80%). Considering their characteristics, planning did not meet the established requirements even when managers indicated that they were strategic (38.9%). When measuring alignment in relation to directives and Law objectives, we inferred that 70% were aligned (strong and moderate alignment). Concerning alignment to Law and Agriculture, Cattle Raising and Supply Ministry, the study shows there is alignment to Law but little alignment to the Ministry (40%). Concerning alignment to Law and Agrarian Development Ministry Planning, the study identified 12 planning projects (12%) aligned to Law and strongly or moderately aligned to the Agrarian Development Ministry directives and strategic objectives. According to the perception of organization senior directors, our study indicates that 64.3% of them believe planning is aligned to the Agrarian Development Ministry and 35.7% believe they are aligned to Agriculture, Cattle Raising and Supply Ministry. Our conclusion is that most organizations are aligned to the Technical Assistance and Rural Extension Law and their focus is family farm, as provided by the Agrarian Development Ministry.